Terobosan Penegakan Hukum Dalam Menangani Ancaman New Psychoactive Substance (NPS) : Adopsi Ketentuan Hukum Internasional - Christiana, Christiana; Mutia, Andriani; Ramdlonaning, Anisya; Fatrika, Slamet (UI Scholars Hub, 2020)
New Psychoactive Substance (NPS) is a substance that is deliberately made in such a way that it has effects similar to Narcotics and psychotropics which pose a threat both globally, regionally and which are harmful to health and can cause social and economic problems with a decrease in the number of productive ages due to or premature death. The development of the NPS which is indicative of transnational organized crime to evade regulation. NPS in Indonesia is also a serious threat as indicated by the number of NPS currently circulating as many as 84 types and the number of confiscations continues to increase. However, the development of the NPS is not regulated by regulations. The method used in this article is a normative juridical approach with secondary data from regulations regarding NPS. Literature study was used as a method of data collection and analysis with an analytical qualitative approach. Of the 84 successful NPS, 9 of them have not been regulated. The irony is that the 9 NPS that have not been regulated are the types of NPS that are widely circulating in Indonesia, because in handling it, a new breakthrough is needed in the prosecution of NPS cases. Law enforcers can adopt the rules of international law that are already in effect. For example, a list of NPS issued by international institutions (UNODC, EMCDDA) or regulations related to NPS that have been issued by other countries as Narcotics. Keywords: New Psychoactive Substance, Nps, Legal Regulations, International Law Provisions And Drugs